The fundamentals of printed textile design - Russell, Alex. (Lausanne ; Worthing : AVA Academia, 2011)
Explores practice in printed textile design. This title provides an introduction to the creative skills, techniques and processes required by designers in order to produce a professional, creative and commercially aware portfolio. It outlines the process of creating designs, looking at the vital role played by drawing, colour, style and content.
boek